Brachiobasilic Fistula at Manmohan Center: A Retrospective Review - Shrestha, Kajan R; Gurung, Dinesh; Shrestha, Uttam K (Journal of Institute of Medicine Nepal, 2019)
Introduction: Brachiobasilic fistula (BBF) with transposition is one of methods for creating native arteriovenous fistula (AVF) for hemodialysis. This study aims to highlight the result of a BBF in a tertiary referral center and aims to improve its result. Methods: This is a retrospective descriptive study conducted on the basis of data collected of patients undergoing BBF with transposition from January 2014 to December 2018 (5 years) at Manmohan Cardiothoracic Vascular and Transplant Center (MCVTC). Data regarding demographics, results and complications has been analyzed. Results: Total 59 patients underwent brachiobasilic fistula performed by 3 surgeons with male to female ratio of approximately 3:2 with mean age of patient 68.78±13.77 years. Hypertension was the most common comorbidity present in 91.53% (54) of patients. Fifty six (94.92%) patient had previous undergone some sort of arteriovenous fistula creation and in 10 (16.95%) patients it was done in two stages. There were 2 immediate failures (within 1 week) and 9 early failures (before 1st dialysis) however 2 patients presented later with blocked BBF after starting dialysis. Only 31 patients could be followed up with patent BBF after 1 year of creation. About 71.19% of fistulas were able to mature and undergo dialysis by 6 week period and most common complication was bleeding from incision site in 20 patients (33.90%). Conclusion: Brachiobasilic fistula is the good option for native arteriovenous fistula access for hemodialysis but it need proper selection of cases to decrease complication rates.